Optimization of Online Learning with A Combination of Offline Practices in the Post-Pandemic Era - Koeswanti, Henny Dewi (International Journal of Elementary Education, 2021)
The Covid-19 pandemic has been going on for approximately one year in Indonesia and has had various impacts in all aspects of life, including the impact on education. The Covid-19 pandemic has led to the birth of online learning methods through the implementation of distance learning. This is a new style and previously rarely done by Indonesians who are accustomed to face-to-face learning. The research method used in this article is a qualitative descriptive which provides an overview of online learning problems as well as solutions and efforts to optimize learning both online and offline. The result of this study is that in the post-pandemic period, online learning can be conducted combined with offline activities for students by applying health protocol standards in their homes.